2008
DOI: 10.1007/s10230-007-0028-y
|View full text |Cite
|
Sign up to set email alerts
|

Field-scale demonstration of the potential for sewage to remediate acidic mine waters

Abstract: Pit lake waters are often contaminated by acid mine drainage (AMD) from weathering of pyritic materials exposed by mining operations, leading to low pH, and high solute and heavy metal concentrations. Few cost-effective engineering solutions exist for large-scale environmental remediation of AMD-contaminated pit lakes. However, various studies have demonstrated that biological remediation strategies for remediating AMD-contaminated waters, including microbially-mediated sulphate reduction, show promise at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Geller and Schultze 2013) or mixing with organic-rich sewage (e.g. McCullough et al 2008). These approaches may well be more costeffective than the method proposed here when the only aim is water treatment.…”
Section: A Proposed Process For Redeveloping Open Pits As Long-term Cmentioning
confidence: 98%
“…Geller and Schultze 2013) or mixing with organic-rich sewage (e.g. McCullough et al 2008). These approaches may well be more costeffective than the method proposed here when the only aim is water treatment.…”
Section: A Proposed Process For Redeveloping Open Pits As Long-term Cmentioning
confidence: 98%
“…In laboratory microcosm studies, Van Hille et al (1999) used MWW to create algae-rich high pH water, which was mixed with AMD. McCullough et al (2008) documented water quality improvement due to BSR in an evaporation pond in which high-strength AMD was accidentally introduced to secondary MWW. Strosnider and Nairn (2010) found that incubating AMD with MWW, with and without limestone, could decrease acidity and create alkalinity.…”
Section: Introductionmentioning
confidence: 97%
“…Waybrant et al (1998) observed that sewage sludge encouraged higher levels of SO 4 2-reduction than seven other commonly used organic carbon sources. However, studies have noted that mixtures of MWW sludge with multiple organic carbon sources generally promote higher SO 4 2-reduction rates than single sources (McCullough et al 2008;Waybrant et al 1998). MWW contains a wide variety of organic compounds ranging from simple sugars to more recalcitrant compounds, such as cellulose (Metcalf and Eddy, Inc 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Techniques like the co-treatment of municipal wastewater (with biosolids as byproducts) and AMD has recently gained popularity following its introduction by Roetman [39], when it was proposed to remove pathogens in sewage [40]. Results from studies to date have shown the removal of metals, certain nutrients, increases in pH and alkalinity, and overall water/leachates quality improvements [41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%